Pemanfaatan Air Lindi Sebagai Aktivator Kompos Metode Takakura - Vidia Nuria Rahman; Devi Safira Damayanti; Septa Indra Puspikawati (Sanitasi: Jurnal Kesehatan Lingkungan, 2022)
Waste is a product of human activity in the form of residual and unwanted existence. Utilization of leachate as a bio activator is an alternative to utilizing leachate from waste piles into something useful for processing organic waste into compost. The study aimed to determine whether or not there was a significant difference in the growth rate of composted tomato plants with leachate activator and compost without activator. The research method used a semi-quasi-experimental design with a treatment group and a control group and composting for 30 days and testing on plants for 15 days. Statistical analysis using the Independent Sample T-Test. The result of this research is that compost with 45 ml of leachate activator produces compost with a pH of 7.5, a final temperature of 31oC, and a final humidity of 60%. The results of the Independent Sample T-Test test on plant height produced p-value (sig) = 0.467> 0.05 and on the number of plant leaves produced p-value (sig) = 0.481> 0.05. The study concluded that the results of compost with a leachate activator of as much as 45 ml did not meet the requirements of SNI 19-7030-2004 and there was no significant difference in the average growth of compost tomato plants with a leachate activator and compost without an activator so it can be concluded that the leachate activator was 45 ml has no significant effect on compost quality and tomato plant growth.